Injury rate in professional soccer players within the community of Madrid: A comparative, epidemiological cohort study among the First, Second and Second B Divisions - Garcia-Fernández, P.; Guodemar-Pérez, J.; Ruiz-López, M.; Rodriguez-López, E.; Hervás-Pérez, J. P. (Journal of Physiotherapy & Physical Rehabilitation, 2017)
Background: Soccer is a sport with international reach and presence. Injury rates in this sport are high, and these have a high economic impact on soccer clubs. Objectives: To report the incidence, type and circumstances of injuries sustained by professional soccer players in Spain across three playing categories: first division, second division, second division B. Study design: A prospective, descriptive, epidemiological cohort study. Participants: The inclusion criteria consisted of all male players with an existing contract within the first team. Players with old injuries were not excluded and neither were those who were injured when data collection began. The number of players in the sample included 100 professional soccer players. Methods: This prospective, observational study examined time-lost injuries occurring during 2016/2017 season among 100 male players from 4 soccer clubs based on a comprehensive data recording form. Main Outcome Measurements: Date and mechanisms of injury, body area injured, diagnosis, severity, and time-off (days) for each player were collected. Results: 142 injuries were recorded. The injury incidence rate was 2.58 injuries per 1000 hours exposure. The number of injuries decreased the higher the professional category, thus a statistically significant difference was found with a greater number on injuries in the second division B players (3.03) compared to first division (2.27) and second division (1.92). Direct player-to-player contact was responsible for 66.9% of injuries. The majority (80.98%) of injuries occurred in the lower limb, of which the thigh was the most injured area (40%) followed by the knee (19.13%). Muscle injuries were the most frequent form of injury (52.10%), of which the hamstrings were the most affected muscle. Conclusion: These findings help identify the most common injury patterns. This data may be used to improve current injury prevention programs.